Serum cholesterol and risk of high-grade prostate cancer: results from the REDUCE study. Issue 2 (June 2018) - Jamnagerwalla, Juzar; Howard, Lauren; Allott, Emma; Vidal, Adriana; Moreira, Daniel; Castro-Santamaria, Ramiro; Andriole, Gerald; Freeman, Michael; Freedland, Stephen J.
Abstract Background Epidemiologic evidence for a serum cholesterol-prostate cancer link is mixed. Prostate-specific antigen (PSA) is positively correlated with cholesterol, potentially increasing PSA-driven biopsy recommendations in men with high cholesterol, though biopsy compliance may be lower in men with comorbid conditions. These potential biases may affect PSA-driven biopsy rates and subsequent prostate cancer detection in men with high serum cholesterol. Our objective was to test the association between serum cholesterol and prostate cancer risk in men receiving PSA independent, study-mandated prostate biopsies. Methods We conducted a post hoc analysis of data from 4974 non-statin users in REDUCE, a randomized trial in men with elevated PSA and a negative baseline biopsy. Men underwent 2- and 4-year trial-mandated prostate biopsies. Associations between baseline serum levels of total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL) and prostate cancer risk, overall and by Gleason grade (<7 vs. ≥7), were examined using multivariable logistic regression. Results High total serum cholesterol was associated with an increased risk of high-grade prostate cancer diagnosis (OR per 10 mg/dL 1.05; 95% CI 1.00–1.09;p  = 0.048), but cholesterol was unrelated to either overall or low-grade prostate cancer risk (p -values >0.185). There was no association between serum LDL and overall, low- or high-grade prostate cancer risk (p -values >0.137). In contrast, elevated serum HDL was associated with increased risk of both overall (OR per 10 mg/dL 1.08; 95% CI 1.01–1.16;p  = 0.033) and high-grade prostate cancer (OR per 10 mg/dL 1.14; 95% CI 1.01–1.28;p  = 0.034). Conclusions In REDUCE, where all men received PSA independent, trial-mandated biopsies thus ensuring complete prostate cancer ascertainment, high total serum cholesterol and high HDL were associated with increased risk of high-grade prostate cancer, supporting a cholesterol-prostate cancer link.